Primary headache subtypes and thyroid dysfunction: Is there any association? - SPANOU, Ioanna; CHRISTIDI, Foteini; LIAKAKIS, Georgios; RIZONAKI, Konstantina; BOUGEA, Anastasia; ANAGNOSTOU, Evangelos; KARARIZOU, Evangelia (Arquivos de Neuro-Psiquiatria, 2020)
Background: Primary headaches, and particularly migraine and tension-type headache (TTH) as well as hypothyroidism are common medical conditions. To date, numerous studies have suggested a possible bidirectional relationship between migraine and hypothyroidism, although certain studies had contradictory results. Objective: To investigate whether there is any association between primary headache subtypes and thyroid disorders. Methods: A retrospective study of consecutive patients aged ≥18 years referred to the Headache Outpatient Clinic of Aeginition Hospital and diagnosed with primary headache and any thyroid disorder. Results: Out of 427 patients (males/females=76/351), 253 (59.3%) were diagnosed with migraine without aura, 53 (12.4%) with TTH, 49 (11.5%) with migraine with aura, 29 (6.8%) with medication-overuse headache, 23 (5.4%) with mixed-type headache (migraine with/without aura and TTH), nine (2.1%) with cluster headache, and 11 (2.6%) with other types of primary headaches. The prevalence of any type of thyroid disorder was 20.8% (89/427 patients). In the total sample, 27 patients (6.3%) reported hypothyroidism, 18 (4.2%) unspecified thyroidopathy, 14 (3.3%) thyroid nodules, 12 (2.8%) Hashimoto thyroiditis, 12 (2.8%) thyroidectomy, three (0.7%) thyroid goiter, and three (0.7%) hyperthyroidism. Further statistical analysis between categorical variables did not reveal any significant association between headache subtypes and thyroid dysfunction. Conclusions: No specific association was found between primary headache subtypes and specific thyroid disorder. However, a high prevalence of thyroid dysfunction in general and specifically hypothyroidism was demonstrated among patients with primary headaches, which lays the foundation for further clarification in prospective longitudinal studies.
Keywords: Headache; Migraine Disorders; Tension-type Headache; Thyroid Diseases; Hypothyroidism